Decreased expression of MGMT in correlation with aberrant DNA methylation in esophageal cancer patients from North India - Asad Ur Rehman; Snigdha Saikia; Mohammad Askandar Iqbal; Istaq Ahmad; Sadaf; Afzal Anees; PS Aravinda; Pramod Kumar Mishra; Suresh Hedau; Sundeep Singh Saluja; Subhash Medhi; Syed Akhtar Husain (Tumor Biology, 2017)
O-6-methylguanine-DNA methyltransferase, DNA repair gene, has been found to be involved with the pathogenesis of the esophageal cancer. DNA hypermethylation and other factors have been suggested to downregulate O-6-methylguanine-DNA methyltransferase. In this communication, the methylation status of O-6-methylguanine-DNA methyltransferase gene and the corresponding O-6-methylguanine-DNA methyltransferase protein expression in esophageal cancer from North India has been studied. In all, 80 samples of tumor tissue along with adjacent normal tissue as controls were analyzed for messenger RNA level of O-6-methylguanine-DNA methyltransferase gene, protein expression, and subcellular localization. The messenger RNA expression was studied using real-time quantitative polymerase chain reaction, protein expression, and its subcellular localization by Western blotting and immunohistochemistry. DNA methylation was assessed through methylation-specific polymerase chain reaction. Clinicopathological parameters were recorded and correlated with the O-6-methylguanine-DNA methyltransferase expression. O-6-methylguanine-DNA methyltransferase messenger RNA expression was found to be downregulated in 65% cases (52/80). The expression of O-6-methylguanine-DNA methyltransferase at the protein level was also found to be absent in 65% (52/80) cases. In all, 52 cases had low or no expression of the protein, whereas out of those 28 remaining cases, 11.25% (09/80) cases had high O-6-methylguanine-DNA methyltransferase protein expression. The absence of O-6-methylguanine-DNA methyltransferase protein coincided with the methylated cases in 84% (38/45), whereas in 07 cases, out of the 45 methylated, O-6-methylguanine-DNA methyltransferase protein was present. The aggressive esophageal cancer patients having methylated O-6-methylguanine-DNA methyltransferase had more than 50% cases with no/mild expression of the O-6-methylguanine-DNA methyltransferase protein ( p  > 0.001). Loss of O-6-methylguanine-DNA methyltransferase protein was very frequent in the incidence of esophageal cancer from North Indian patients, and methylation of the promoter region of O-6-methylguanine-DNA methyltransferase was significantly associated in its downregulation.